Modeling and Stability Analysis of Voltage Sense Current Cancellation Active EMI Filter - Haensel, Stefan; Teller, Janina; Frei, Stephan (IEEE International Symposium on Electromagnetic Compatibility, 2023)
This paper introduces a feedback voltage sense current compensation topology for active EMI filters (AEF), which provided good noise suppression and ensures high frequency stability. First, the performance is analyzed mathematically. Design rules for the AEF and all passive components are derived. Secondly, the filter is realized and integrated in a laboratory setup with a 400W AC/DC power supply and analyzed. Between 300 kHz and 2 MHz a reduction of EMI emission of more than 10 dB could be achieved. The measured attenuation of the AEF matches well with the theoretical expectations.
CRIS-Team Scopus Importer:2024-12-16